Validitas dan Reliabilitas Konstruk Pengukuran Perpustakaan Ideal Berbasis Pemakai dengan Pendekatan LIBQUAL - Fahruna, Yulyanti; Fahmi, Muhammad (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2017)
This study aims to measure the validity and reliability construct satisfaction and quality of library services based on the user using LIBQUAL (library quality) method with a touch of marketing management. Data analysis by Cronbach Alpha and Pearson Correlation. The research was conducted in Tanjungpura University (UNTAN) by taking samples of visitors (students) at six (6) faculty libraries namely three (3) social faculty of 150 people and three (3) science faculty of 150 people. The sample is chosen by purposive sampling method. Reliability test results show that the five US, IC, LP, LQ and KU variables show high instrument reliability. The result of pearson correlation test shows that the measurement instrument used has problem validity on some question items. At minimum service item with correlation value smaller than 0.30 is IC2, IC5 and LQ5 so it is declared invalid. At service expectation items with correlation value smaller than 0.30 ie AS8, IC1, IC2, IC4, LP1, KU1, KU2, KU4, and KU8. And at present service items with correlation values smaller than 0.30 ie IC1, IC3, LP1, LP3, LQ1, LQ3, LQ4 and KU1.